Importing a Successful System? Simulating Different Regimes of Financing Social Security for Germany - Caroline Dieckhoener; Andreas Peichl (Institute for the Study of Labor (IZA), 2009)
In Germany, there is an ongoing debate about how to increase the efficiency of the social security system. The aim of this paper is to simulate different financing systems for Germany with its typical Conservative welfare state regime. For our analysis, we rely on the European static multinational microsimulation model EUROMOD, which provides the opportunity to implement the financing systems of other European countries in Germany (policy swap). The introduction of a Liberal British or the Southern Greek financing system increases inequality and poverty, as well as labour supply incentives. The introduction of the Social-democratic Danish financing system decreases inequality of incomes and leads to ambiguous incentives effects. Our results suggest that there is scope for efficiency increasing reforms in Germany although we do not simulate behavioural responses.
Keywords: C81; D31; H24; 330; social security; welfare states; comparative analysis; EUROMOD; Finanzierung der Sozialversicherung; Sozialstaat; Dänisch; Britisch; Griechisch; Simulation; Sozialreform; Wirkungsanalyse; Armut; Ökonomischer Anreiz; Deutschland